Morphological and Physicochemical Properties of Macrocrystalline Talc from Argentine - Barbosa, Silvia Elena (2023)
A detailed petrographical, mineralogical, morphological, geochemical and physicochemical characterization of talc from an Argentinean ore is presented. This deposit is located in the San Juan province at the foothills of the Andes. Characterization was performed on rock and milled talc using different techniques including polarized light microscopy, transmission electron and scanning microscopy with energy dispersive spectroscopy (SEM/EDX), chemical analyses, X-ray diffraction (XRD), X-ray fluorescence, Fourier transform infrared spectroscopy (FTIR), particle size determination by laser diffraction, thermogravimetry analysis, and colorimetry. A mineral sample contains approximately 80 wt% talc. Associated minerals such as carbonates as veins and chlorite interlaminated with talc were detected. Carbonates are calcite, dolomite and magnesite, as was corroborated by FTIR. Morphology and crystallinity were assessed by XRD data, obtaining a morphological index of 0.79 which indicates the macrocrystalline character. Crystalline habits of associated minerals were recognized by SEM, detecting their constitutive elements by EDX. Talc color parameters are L* = 82.76, a* = −1.50, and b* = 5.38. The slight yellowing could be attributed to chlorite or traces of Fe oxides. Although the whiteness index (62.12) impedes its commercialization as a high-priced mineral, this kind of talc can be used as an additive for polymers, since it would offer a high reinforcing effect (improvement of mechanical properties).